(untitled) (Annals of Medical Research, 2021)
Aim: This study was planned to determine the demographic, etiological and clinical characteristics and the treatment costs of the patients with open isolated hand and/or wrist injuries.Material and Methods: In this study, the data of 127 patients who were admitted to the adult emergency department due to hand and / or wrist trauma between 01.01.2018 and 06.30.2018 were examined. Data on demographic data, shape and clinic of injury were summarized as number and percentage. Shapiro Wilk test was used to determine whether the numerical measurements were compatible with the normal distribution and Kruskal Wallis test was used for comparison of cost between groups.Results: Of the patients, 81.1% were male and the most common injury was seen in the age group of 19-64 and workers. Fingers were the most frequently injured areas and the most common injured finger was the index finger. The first two reasons in the aetiology were home and occupational accidents. Penetrating/cutting was the most common injury mechanism. There was no significant difference between occupation groups in terms of cost (p>0.05) but there was a significant difference between diverse treatment methods (p0.0001). Conclusion: Hand and / or wrist open injuries not only represent a significant part of all injuries but also represent a significant economic burden with high health costs. Measures to prevent such injuries could contribute to lowering health expenditures.